2012
DOI: 10.1155/2012/692350
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Studies and Interactions ofPseudomonas syringaePathovars on Wheat

Abstract: Wheat is affected by some pathovars ofPseudomonas syringaeand by otherPseudomonasspecies. Of these,P. syringaepv.syringaeis the major one responsible for reduction. Recent studies have been made to characterize and identify the pathogen and to determine its aggressiveness and the pattern of colonization in seed and its effects on seed yield, yield components, and source-sink relationships during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
0
16
0
2
Order By: Relevance
“…Nevertheless, it has been reported that, out of almost 50 known P. syringae pathovars, P. syringae pv. atrofaciens causes “basal glume blotch” in wheat and barley (Toben et al , 1991; Valencia-Botín and Cisneros-López, 2012), P. syringae pv. syringae causes “leaf blight” in wheat and barley (Toben et al , 1991; Valencia-Botín and Cisneros-López, 2012), P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it has been reported that, out of almost 50 known P. syringae pathovars, P. syringae pv. atrofaciens causes “basal glume blotch” in wheat and barley (Toben et al , 1991; Valencia-Botín and Cisneros-López, 2012), P. syringae pv. syringae causes “leaf blight” in wheat and barley (Toben et al , 1991; Valencia-Botín and Cisneros-López, 2012), P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%
“…atrofaciens causes “basal glume blotch” in wheat and barley (Toben et al , 1991; Valencia-Botín and Cisneros-López, 2012), P. syringae pv. syringae causes “leaf blight” in wheat and barley (Toben et al , 1991; Valencia-Botín and Cisneros-López, 2012), P. syringae pv. japonica can cause blight or striated areas on the nodes (Valencia-Botín and Cisneros-López, 2012), in addition to other Pseudomonads that are known to infect wheat, such as P. cichorii, causing stem or shank melanosis and P. fuscovaginae that induces a black rot in the wheat sheath.…”
Section: Discussionmentioning
confidence: 99%
“…There are also plant beneficial species such as P. chlororaphis that have been utilized as biopesticides to control microbial pathogens, insects, and nematodes ( Anderson and Kim, 2018 ). The plant pathogen P. syringae has been studied for its broad host range in commercial crops and the resulting yield reduction ( Valencia-Botín and Cisneros-López, 2012 ). The opportunistic pathogen P. aeruginosa is known for infecting immunocompromised individuals and has a natural resistance to many antibiotics ( Priebe and Goldberg, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, PGPR have emerged as a promising alternative to increase oxidative stress tolerance and disease resistance in plants (Islam et al, 2014;Pieterse et al, 2014). Wheat (Triticum aestivum) is challenged by several bacterial pathogens, which can cause severe diseases and pests (Valencia-Botín and Cisneros-López, 2012). The pathogen Pseudomonas syringae pv.…”
Section: Introductionmentioning
confidence: 99%